ANALISIS SELF ASSESMENT SYSTEM, OFFICIAL ASSESSMENT SYSTEM DAN WITHHOLDING ASSESMENT SYSTEM TERHADAP KEPATUHAN FORMAL WAJIB PAJAK - Octavia Rosa Indriana; Fauzan (JURNAL ILMIAH EDUNOMIKA, 2025)
This study aims to find out how formal taxpayer compliance is impacted by the official assessment, withheld assessment, and self-assessment methods, as well as any potential roadblocks. This study used primary data as its data type. By selecting 100 respondents from the general public, the data was collected directly from taxpayers who were registered at the Karanganyar Pratama Tax Office (KPP Pratama Karanganyar). Convenience sampling was the sampling method employed. The study's data source was a questionnaire that was distributed to individual taxpayers who were enrolled at the Karanganyar Pratama Tax Office. The scores for every indicator variable were also included in the questionnaire. The findings of this study corroborate those of Endang's (2017) investigation, which found that as trust is the foundation of an activity, it is one of the most crucial factors for tax officials to take into account when trying to improve taxpayer compliance. If taxpayers think that tax authorities are opportunistic or self-serving, they will be unwilling to pay taxes. According to the author's research, the previous multiple linear analysis results produced a constant value of 2.88 with positive parameters, meaning that the compliance variable's value would have increased by 2.88 if all independent variables or x were zero. Keywords : Self Assesment System, Official Assessment System, Withholding Assesment System, Formal Taxpayer Compliance